EFFECTIVE POPULATION AND INBREEDING RATE PER GENERATION OF BALI CATTLE IN TEON NILA SERUA DISTRICT: UKURAN POPULASI EFEKTIF DAN LAJU SILANG DALAM PER GENERASI SAPI BALI DI KECAMATAN TEON NILA SERUA - Lakotani, Jacob W.; Rajab, Rajab; Papilaya, Bercomien J. (Universitas Djuanda, 2024)
The aim of the study was to determine the effective population size and cross-over per generation of Bali cattle in Teon Nila Serua District, Central Maluku Regency. The method used in this study was a survey method by interviewing 10 respondents in each sample village which were randomly selected (random sampling), and direct observation in the field. The observed variables included population structure, actual population, effective population size, and cross-over rate per generation. The results showed that the effective population size of Bali cattle in TNS District was dominated by adult cows as breeding stock to maintain and increase the population with an inbreeding rate per generation of Bali cattle in Teon Nila Serua District which was still low indicating that the condition of the Bali cattle population was still in the status of safe to develop